EFEKTIFITAS ICE BREAKING TERHADAP PENINGKATAN PRESTASI BELAJAR SISWA KELAS II DI SDN PANDEANLAMPER 03 SEMARANG - Reski Wening Asmarani; Ervina Eka Subekti; Ida Dwijayanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The achievement of educational goals is inseparable from the success of the learning and teaching process in schools. Until now the homeroom teacher applies conventional methods, namely lectures for learning which results in students being less active. Lack of teacher innovation in the use of learning methods will create uninteresting learning which will make students unable to concentrate and cause understanding of the material to be less than optimal. One of the fun learning methods is ice breaking, through the Problem Basic Learning learning model. The aim of the research is to describe the effectiveness of ice breaking on improving student achievement in class II. This type of quantitative research is experimental in nature, one group pretest and posttest design approach and uses a saturated sampling technique, namely making all members of the population as samples. Test questions are research instruments whose goal is to obtain data on student achievement. The results showed that the pretest average was 74,62 while the posttest average was 88,08 which means that there was an increase in student achievement after the implementation of ice breaking of 13,46. In order to find out the effectiveness of ice breaking, data analysis was carried out using the Wilcoxon test. The result is a significance value of 0,000 < 0,05 so that Ha is accepted and H0 is rejected. With these results, ice breaking was effective in increasing class II student achievement at SDN Pandeanlamper 03 Semarang.